Contamination of Salmonella Sp. in Broiler Meat Sold In Traditional Markets of Banjarbaru City - Herliani, Herliani; Langai, Bambang F; Hidayat, Muhammad Ilmi; Hidayat, Adinda Anina Apriliyani; Aulia, Muhammad Dhiyaul (Jurnal Veteriner; Vol 25 No 4 (2024)DO - 10.19087/jveteriner.2024.25.4.485, 2025)
Meat is an important food commodity in meeting nutritional needs. Damage that leads to a decrease in the quality of fresh meat is mainly caused by microorganisms. One of  the  pathogenic  bacteria  that  can  contaminate  broiler  meat  is  Salmonella  sp.  This research  aims  to  determine  the  food  safety  level  of  broiler  meat  sold  in  traditional markets  in  the  city  of  Banjarbaru  regarding  contamination  by  Salmonella  sp.  bacteria and  to  prevent  the  circulation  of  poultry-origin  products  (broilers)  that  do  not  meet  the required  standards,  which  can  threaten  consumer  health.  The  research  method  used  in this  study  is  a  survey  and  laboratory  analysis.  This  study  utilized  56  chicken  meat samples  from  4  traditional  markets  using  a  random  sampling  method.  The  test  results showed  that  18  samples  were  contaminated  with  Salmonella  sp.  bacteria  out  of  the  56 samples. This indicates that the quality of chicken meat sold in some traditional markets, 32.14%,  does  not  meet  the  standards  based  on  the  Indonesian  National  Standard  for chicken meat (SNI 7388:2009)